Deep Diving Into the Cardiovascular Health Paradox: A Journey Towards Personalized Prevention - Bamba Gaye; Bamba Gaye; Nabila Bouatia Naji; Mario Sims; Yendelela Cuffee; Oluwabunmi Ogungbe; Erin D. Michos; Camille Lassale; Camille Lassale; Camille Lassale; Pierre Sabouret; Pierre Sabouret; et al. (Frontiers Media S.A., 2024)
ObjectivesThe Life's Simple 7 score (LS7) promotes cardiovascular health (CVH). Despite this, some with optimal LS7 develop cardiovascular disease (CVD), while others with poor CVH do not, termed the "CVH paradox." This paper explores pathways explaining this paradox.MethodsWe examined methodological aspects: 1) misclassification bias in self-reported lifestyle factors (smoking, physical activity, diet); 2) cumulative exposure to risk factors over a lifetime, impacting the CVH paradox. Punctual risk factor assessments are suboptimal for predicting outcomes. We proposed personalized prevention using "novel" elements to refine CVH assessment: 1) subclinical vascular disease markers, 2) metabolic biomarkers in blood and urine, 3) emerging risk factors, 4) polygenic risk scores (PRS), 5) epigenetics, and 6) the exposome.ResultsAddressing the CVH paradox requires a multifaceted approach, reducing misclassification bias, considering cumulative risk exposure, and incorporating novel personalized prevention elements.ConclusionA holistic, individualized approach to CVH assessment and CVD prevention can better reduce cardiovascular outcomes and improve population health. Collaboration among researchers, healthcare providers, policymakers, and communities is essential for effective implementation and realization of these strategies.